Secreted Frizzled Related Proteins in Cardiovascular and Metabolic Diseases - Guan, Hua; Zhang, Jin; Luan, Jing; Xu, Hao; Huang, Zhenghao; Yu, Qi; Gou, Xingchun; Xu, Lixian (Frontiers in Endocrinology, 2021)
Abnormal gene expression and levels of secreted proteins are accompanied by extensive pathological changes. Secreted frizzled related protein (SFRP) family members are antagonistic inhibitors of Wnt signaling pathway. Recently, SFRPs are found to be involved in the pathogenesis of a variety of metabolic diseases. This recent breakthrough drew extensive attention and interest in SFRPs. Previous reports highlighted the importance of SFRPs in lipid metabolism, obesity, type 2 diabetes mellitus and cardiovascular diseases. In this review, we provide a detailed introduction of SFRPs, including the structural characteristics, receptors, inhibitors, signaling pathways and the effect on metabolic diseases. In addition to summarizing the pathologies and potential molecular mechanisms associated with SFRPs, this review extends further to suggest a potential use of SFRPs as biomarkers for diseases and therapeutic targets in future.